Kobiety i twórczość muzyczna w prozie autobiograficznej - Czerska, Tatiana (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The essay deals with the problem of the presence of women in music. In the history of the culture, art above all, women have traditionally constituted the object of artistic creation, not the creator. Particularly valuable material for research may prove female autobiographical writing. The selected works of Polish authors are analyzed through the categories of gender discourses. The paper is an attempt to show cultural changes associated with the feminine approach to musical creation. In the nineteenth century, we can talk about the formation of a kind of salon women's subculture. The turn of the modernist and the First World War mean the cultural advancement of women. We can talk about the expansion of women in the culture, and thus in the music. In analyzed memories appear women practicing music only in the private sphere: the home or giving lessons, even if some of them the ability to play an instrument is a passion. The autobiographical prose seem to confirm that women were determined to develop his artistic passion had to choose between art and family.